Czy „Polacy są Irlandczykami kontynentu...”? - Wróbel, Marzena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
There are certain similarities between Poland and Ireland, namely the long history of struggling for independence, difficult relationship with their stronger neighbors in the past and certain distrust towards them in the present, attachment to Catholicism (and its relation to the national identity), mass emigration waves and poor economic structure, based on small farms, at the time of joining the EU structures. However, this relative similarity of the history of both countries (which are perceived as referring to their history to an excessive degree) and shared experience cannot provide an answer to the question whether Poland in the EU will follow the successful Irish path. The answer should be sought in bold economic programs, their consistent implementation and in the achievement of the goals set.